2022
DOI: 10.1021/acsnano.2c07876
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Gating of the Charge-Density-Wave Phases in Two-Dimensional h-BN/1T-TaS2 Devices

Abstract: We report on the electrical gating of the charge-density-wave phases and current in h-BN-capped three-terminal 1T-TaS2 heterostructure devices. It is demonstrated that the application of a gate bias can shift the source–drain current–voltage hysteresis associated with the transition between the nearly commensurate and incommensurate charge-density-wave phases. The evolution of the hysteresis and the presence of abrupt spikes in the current while sweeping the gate voltage suggest that the effect is electrical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The hysteresis observed by applying the forward and reverse electric bias clearly reveals the NC‐CDW to IC‐CDW phase transition, in line with prior reports. [ 12,16,18–21,33–36,39–44 ] These results confirm that the filler material we used for the preparation of quantum composites is of high quality, with a well‐defined and pronounced CDW phase transition.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The hysteresis observed by applying the forward and reverse electric bias clearly reveals the NC‐CDW to IC‐CDW phase transition, in line with prior reports. [ 12,16,18–21,33–36,39–44 ] These results confirm that the filler material we used for the preparation of quantum composites is of high quality, with a well‐defined and pronounced CDW phase transition.…”
Section: Resultssupporting
confidence: 61%
“…The details of fabricating the Ohmic contacts to 1T-TaS 2 samples for the electrical measurements have been reported by some of us elsewhere. [14,40,41] In Figure 1d, we present the representative current-voltage (I-V) characteristics of a singlecrystal few-layer of 1T-TaS 2 measured at room temperature. The hysteresis observed by applying the forward and reverse electric bias clearly reveals the NC-CDW to IC-CDW phase transition, in line with prior reports.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the larger contribution from the topmost six Se atoms, the SODs are imaged as triangular protrusions, as labeled by the blue triangles in Figure 1a, and thereafter. Due to the trend for continuous minimization of CDW-based electronic devices, [21][22][23] it is intuitive to explore how would the CDW patterns behave on the nanoscale NbSe 2 islands, especially when island size is comparable to several CDW units.…”
Section: Resultsmentioning
confidence: 99%
“…3 In recent years, the layer-dependent photoluminescence (PL) property of layered WSe 2 has been studied; particularly, as the thickness decreases to a monolayer, the transition from indirect to direct gap has been observed by PL measurements. 4 Up to now, various methods, including ionic-liquid gating 5 and hexagonal boron nitride capping, 6 have been investigated for improving both carrier mobility and PL efficiency of TMDCs. For instance, Yamamoto et al reported that exposure of WSe 2 to O 3 at 100 °C for a few hours formed the selective oxidation layer by providing protection from ambient effects, while this treatment resulted in a decrease in PL intensity and damage to the underlying layers of the materials.…”
Section: Introductionmentioning
confidence: 99%